2003
DOI: 10.1038/oby.2003.7
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Human Daily Physical Activity

Abstract: ]. Postures, limb movements, and jumping were tested using a timed protocol of specific activities. Walking and running were tested using a 60-meter track, on which subjects walked and ran at 6 self-selected speeds. Stair climbing and descending were tested by timing subjects who climbed and descended a flight of stairs at two different speeds. Results: Correct identification rates averaged 98.9% for posture and limb movement type and 98.5% for gait type. Pooled correlation between predicted and actual speeds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
221
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 271 publications
(231 citation statements)
references
References 15 publications
(18 reference statements)
2
221
1
2
Order By: Relevance
“…Advances have, however, been made in accelerometer data processing with the development of more sophisticated approaches to data modelling analysis (Bonomi et al 2009, Pober et al 2006, Staudenmayer et al 2009, Zhang et al 2003. This area warrants further investigation in studies of pre-school children to determine if this will offer an accurate means of classifying physical activity behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…Advances have, however, been made in accelerometer data processing with the development of more sophisticated approaches to data modelling analysis (Bonomi et al 2009, Pober et al 2006, Staudenmayer et al 2009, Zhang et al 2003. This area warrants further investigation in studies of pre-school children to determine if this will offer an accurate means of classifying physical activity behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…Besides these commercially available accelerometers, other activity monitors made up by multiple units have been presented in the literature: the Intelligent Device for Energy Expenditure and physical Activity (IDEEA), 43 the Physical Activity Monitoring System (PAMS) from James Levine's research group, 14,44 the Wockets activity monitor from Stephen Intille's research group, 45 and the activity monitor from Henk Stam's and Hans Bussmann's research group. 46,47 Piezocapacitive and piezoresistive accelerometers are usually more obtrusive than piezoelectric ones, have a shorter battery life and are often not integrated in a single device, but their accuracy is much higher as they can monitor multiple aspects of physical activity.…”
Section: Piezoelectric Accelerometersmentioning
confidence: 99%
“…Studies based on several accelerometers showed very high classification accuracy for the detection of postures and different types of ambulatory and cycling activities. 45 Zhang et al 43 showed that the IDEEA, an activity monitor made up of five accelerometers, had a classification accuracy of more than 98% for recognizing 32 types of activity and posture using an artificial neural network algorithm. Bussman et al [49][50][51][52] reported that the activity monitor developed by their research laboratory, consisting of four accelerometers placed in different body locations, had an agreement rate of 89-90% with video observation in detecting a series of nine dynamic movements and different types of posture.…”
Section: Activity Recognition Using Multiple or Single-site Accelerommentioning
confidence: 99%
See 1 more Smart Citation
“…The device can analyze gait, speed, distance, power, work, and energy expenditure. Investigations into the IDEEA 1 system's accuracy show it is accurate for measuring energy expenditure, postures and limb movements, and speed of walking and running [58,59,64,65]. The original IDEEA 1 system was modified for this experiment by adding two electrogoniometers.…”
Section: Introductionmentioning
confidence: 99%